The Incidence, Prevalence, and Mortality of Stroke in France, Germany, Italy, Spain, the UK, and the US: A Literature Review - Younan Zhang; Ann-Marie Chapman; Melanie Plested; Daniel Jackson; Francisco Purroy (Stroke Research and Treatment)
Background. Although the burden of stroke in terms of mortality and disability has been well documented in previous years, data after 2000 are limited. Therefore, the aim of this paper was to identify the epidemiology of stroke in the US and EU5 nations from data published in 2000 and later. Methods. Data from literature databases and online sources were collated to identify information relating to the incidence, prevalence, and mortality of stroke from the year 2000 onwards. Results and Conclusions. Twenty-three data sources were identified. The incidence of and mortality due to stroke both increase with age and are greater in males compared to females. Stroke is a common problem and likely to worsen in the US and EU5 as their populations age. However, pre-2000 trends of decreasing stroke mortality over time have continued after 2000, reflecting a consistent improvement in the treatment and care of patients with stroke.